Implementasi Sistem Informasi Reservasi Hotel Syariah di Kota Jambi Berbasis Website - Purnama, Fery; Ikhsan, Muhammad; Syah, Tamrin (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Al-Fath Hotel located in Jambi City is one of the Jasmine 2 syariah hotels located in Jambi City, and is a growing hotel and continues to strive to improve hotel services and quality standards from various sides, including the use of information technology. The Hotel Reservation information system is a system that can support the level of fluency in carrying out Hotel reservation activities. In room rentals often experience errors in making reports specifically to calculate the number of reports staying overnight. This study aims to develop the Al-Fath Jambi Hotel Reservation Information System, which will be easier in promoting and marketing. Making this Website uses Adobe Dreamweaver CS5 tools, MySQL as its database and CSS Bootstrap so that the display is more attractive and responsive. Inputs from the system are input guest data, room type data, booking data, room data, transaction data and photo data. The process carried out on input data is the booking process, guest process, and transaction process. The system output is information about transaction data reports. Results of the Information System Research Reservation Al-Fath Jambi Hotel can assist the hotel in processing reservation data.